Pubertas Prekoks Perifer Isoseksual akibat Juvenille Granulosa Cell Tumor - Santosa, Putu Adi; Widijanti, Anik; Susianti, Hani; Engli, Katherina Alfa (MEDICINUS, 2020)
A 16-month-old girl with peripheral isosexual precocious puberty due to juvenile granulosa cell tumor underwent unilateral salpingo-oophorectomy procedure to stop the symptoms of precocious puberty. The diagnosis was established based on the patient’s medical history, physical findings, laboratory and other examinations which demonstrated secondary sexual characteristics according to Tanner scale M3P2, presence of abdominal mass, elevated serum estradiol, and a histological finding of juvenile granulosa cell tumor. Karyotyping results was normal. Left salpingo-oophorectomy successfully reduced estradiol concentration and stop the menstruation, while the other secondary sexual characteristics is monthly assessed at the clinic.